Essential interoperability standards : interfacing intellectual property and competition in international economic law - Brinsmead, Simon, 1975- (Cambridge : Cambridge University Press, 2021)
A new international instrument is needed to address access to interoperability standards and standards-essential intellectual property, which are critical to maintaining technological advancement and promoting cost-effective solutions for consumers. Applying law and economics methodologies, Simon Brinsmead systematically explores how international and domestic law deals with these matters. This important book includes an examination of the technical and economic nature of interoperability standards; a detailed analysis of the issues arising under intellectual property and competition law; an analysis of whether liability or exclusive property rules should apply with respect to interoperability standards and SEIP; and consideration of feasible international approaches. Finally, Brinsmead includes a draft of his proposed international soft law instrument as a starting point for future discussions in the field. Of interest to lawyers, regulators and scholars, this work offers a meaningful contribution to international governance, harmonization of laws and technological advancement.
Introduction -- Standards and interoperability standards -- Interoperability standards and international economic law -- Interoperability standards and intellectual property -- Interoperability standards and competition law -- Exclusive property rules or liability rules for interoperability standards and standards essential intellectual property? -- Access to interoperability standards and standards-essential intellectual property : international dimensions -- Concluding observations -- Draft expert manual.
Title from publisher's bibliographic system (viewed on 26 Oct 2021).
Keywords: Internetworking (Telecommunication) -- Law and legislation; Antitrust law; Intellectual property